Patient Perspectives on a Patient‐Facing Tool for Lung Cancer Screening - Victoria L. Tiase; Grace Richards; Teresa Taft; Leticia Stevens; Christian Balbin; Kimberly A. Kaphingst; Angela Fagerlin; Tanner Caverly; Polina Kukhareva; Michael Flynn; Jorie M. Butler; Kensaku Kawamoto (Wiley, 2024)
ABSTRACT Background Individuals with high risk for lung cancer may benefit from lung cancer screening, but there are associated risks as well as benefits. Shared decision‐making (SDM) tools with personalized information may provide key support for patients. Understanding patient perspectives on educational tools to facilitate SDM for lung cancer screening may support tool development. Aim This study aimed to explore patient perspectives related to a SDM tool for lung cancer screening using a qualitative approach. Methods We elicited patient perspectives by showing a provider‐facing SDM tool. Focus group interviews that ranged in duration from 1.5 to 2 h were conducted with 23 individuals with high risk for lung cancer. Data were interpreted inductively using thematic analysis to identify patients' thoughts on and desires for a patient‐facing SDM tool. Results The findings highlight that patients would like to have educational information related to lung cancer screening. We identified several key themes to be considered in the future development of patient‐facing tools: barriers to acceptance, preference against screening and seeking empowerment. One further theme illustrated effects of patient-provider relationship as a limitation to meeting lung cancer screening information needs. Participants also noted several suggestions for the design of technology decision aids. Conclusion These findings suggest that patients desire additional information on lung cancer screening in advance of clinical visits. However, there are several issues that must be considered in the design and development of technology to meet the information needs of patients for lung cancer screening decisions. Patient or Public Contribution Patients, service users, caregivers or members of the public were not involved in the study design, conduct, analysis or interpretation of the data. However, clinical experts in health communication provided detailed feedback on the study protocol, including the focus group approach. The study findings contribute to a better understanding of patient expectations for lung cancer screening decisions and may inform future development of tools for SDM.